Isolated pancreatic tuberculosis presenting as obstructive jaundice - Shafique, Muhammad Salman; Fatima, Sayyam (International Surgery Journal, 2021)
A 36-year-old male patient presented in surgical clinic with complaints of abdominal pain and progressively increasing yellowish discoloration of his skin and sclera for last 1 month. He was deeply jaundiced with mild tenderness in epigastric region. He had a strong family history of tuberculosis. Diagnostic work-up revealed obstructive jaundice secondary to pancreatic tuberculosis. Tomographic examination revealed a pancreatic head mass with peripancreatic lymphadenopathy. Endoscopic ultrasound (EUS) showed a mass at pancreatic head region & EUS guided fine needle aspiration revealed tuberculosis. Patient was started on anti-tubercular therapy with gradual improvement of symptoms over the course of treatment.